(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
Tellurium is a critical element which is utilized in high-tech industries, mainly in solar cells, semiconductors and thermo electrics. In spite of its importance, tellurium extraction is a challenge due to its low abundance and complex processing. This study analyzes some of tellurium extraction methods and compares their technical efficiency, economic viability, and environmental impact. The most effective method is identified based on these factors, providing insights for industrial-scale applications.